Divergent Attitudes among Domestic Violence Risk Assessors and County Welfare Agency Staff during the Family Violence Option Process. Issue 2 (14th March 2020) - Johnson, Laura; Postmus, Judy L.; Hetling, Andrea; Steiner, Jordan; Riordan, Annette; Braasch, Larry
ABSTRACT: This study examined the collaboration between welfare agencies and domestic violence organizations in their effort to implement the Family Violence Option (FVO), which provides states with the option of providing waivers to survivors of domestic violence from Temporary Assistance for Needy Families requirements. Focus groups were conducted with 48 participants from the state human services office, county welfare agencies, and domestic violence organizations. While study findings are state-specific and thus not generalizable, the results can be used to refine our understanding of the needed components of a successful collaboration between public and nonprofit agencies in the implementation of the FVO.